A fluorescent probe for colorimetric detection of bisulfite and application in sugar and red wine - Chen, Haitao (Food Sci Biotechnol, 2019)
A new fluorescent probe made from (E)-2-(benzo[d]thiazol-2-yl)-3-(6-hydroxynaphthalen-2-yl) acrylonitrile (Probe 1) was synthesized for the determination of bisulfite concentrations in real food samples (red wine and sugar). Adding bisulfite to a Probe 1 solution caused a marked decrease in fluorescence intensity and a visual color change from yellow to light yellow. This distinct color response indicates that Probe 1 could be used as a visual sensor for bisulfite. Probe 1 can detect bisulfite quantitatively in the range 0–400 μM with a detection limit of 0.10 μM. This makes Probe 1 a convenient signaling instrument for determining bisulfite levels in sugar and red wine samples. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s10068-019-00571-2) contains supplementary material, which is available to authorized users.